Perbandingan Pengelolaan Pendidikan Agama Pada Sekolah di Indonesia dan Sekolah Republik Indonesia Tokyo - Nurudin, Nurudin; Nurudin (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Religious education is a mandate of national legislation that should be implemented in every school based on the Legislation of National Education System, and as the right of every student to receive religious education in accordance with their own religion. This research is aimed to get sufficient data and information on the management of religious education in the school of the Republic of Indonesia in Tokyo Japan. Specifically, this study is expected to be a policy matter, Firstly, students’ right fulfillment aspect to receive religious education as stated in Legislation Number 20/2003 About the National Education SystemArticle 12 Verse (1) point a. Government Regulation Number 55/2007 about religious education and Religious affair education, and also the Minister of Religious AffairsRegulation Number 16/2010 on the Management of Religious Education in Schools; Secondly, the management of religious teachers and religious education learning in order to meet the Education National Standards as the authority of the Ministry of religious affairs that must be implemented optimally in every educational unit.